Does the need for refinement sets of orthodontic clear aligners correlate with professional experience? - Victor de Miranda LADEWIG; Kamila de Oliveira Novais MACHADO; Thaís Maria Freire FERNANDES; Renata Rodrigues de ALMEIDA-PEDRIN; Paula Vanessa Pedron OLTRAMARI; Márcio Rodrigues de ALMEIDA; Ana Cláudia de Castro Ferreira CONTI (Dental Press Journal of Orthodontics)
ABSTRACT Objective: To assess how often orthodontists request additional aligners and correlate this need with professional’s experience. Methods: A questionnaire was sent by instant messaging app (WhatsApp) to 188 orthodontists who answered it voluntarily. Respondents were grouped by experience, including time of orthodontic training (OT), training with aligners (TA) and number of cases treated with aligners (TC). They were also surveyed about the cases in which they recommend aligners. Chi-square tests were used to analyze associations between experience categories and the need for 1 or 2+ refinements, with a significance level set at 5%. Results: At least one refinement was requested in 70.31% of cases. More experienced specialists and those with longer use of aligners requested refinements more often. A second refinement was required in 21.95% of cases, primarily requested by professionals with less experience as specialists and fewer cases treated with aligners. Mild and moderate crowding were the most indicated malocclusions, while extractions and presurgical treatments were the least. Conclusion: Refinements were needed in most cases treated with aligners. Its need is not related to the lack of experience or knowledge of the technique, being mostly requested by more experienced professionals.